A criação da cátedra de medicina tropical no Peru e no Brasil The creation of chairs in tropical medicine in Peru and Brazil - Marta de Almeida (História, Ciências, Saúde: Manguinhos)
Analisa a proposta de criação da cátedra de medicina tropical nas faculdades de medicina da América Latina feita em 1913, por ocasião do 5º Congresso Médico Latino-americano, em Lima. Investiga o processo de institucionalização do ensino médico dessa especialidade no Peru e no Brasil, por meio da atuação de Julián Arce e Carlos Chagas, médicos que se dedicaram à medicina tropical. O foco da análise são as aulas inaugurais ministradas pelos médicos, a primeira em 1916, na Faculdade de Medicina da Universidade de San Marcos, em Lima, e a segunda em 1926, na Faculdade de Medicina do Rio de Janeiro. Pretende-se contribuir para uma análise mais aprofundada dos diferentes sentidos que a medicina tropical teve no Brasil e no Peru. At the 5th Latin American Congress of Medicine, held in Lima, Peru, in 1913, the idea was put forth to establish chairs in Tropical Medicine at medical schools in Latin America. Through reference to the involvement of Julián Arce and Carlos Chagas, physicians devoted to the study of tropical medicine, the article analyzes this proposal and examines the process by which the teaching of the specialty became institutionalized in Peru and Brazil. The focus is specifically on the inaugural classes given by both professors, the former speaking before the University of San Marcos Faculty of Medicine in 1916 in Lima and the latter, before the Rio de Janeiro Faculty of Medicine in 1926. The present study hopes to contribute to a deeper understanding of the distinct meanings assigned to tropical medicine in Brazil and Peru.